Nanocrystalline (NixCo(1-x))3(PO4)2@FeSe2/NF as a promising OER electrocatalyst for alkaline water electrolysis - Christi, Darren Sebastian; Selvaraj, Kaliaperumal (International Journal of Hydrogen Energy, 2024)
Affordable and sustainable hydrogen production is the need of the hour owing to the mounting global pursuit for the hydrogen economy. Water splitting is the premier go -to method to produce green hydrogen at a larger scale in which the half -cell Oxygen Evolution Reaction (OER) demands a larger amount of energy expenditure due to its sluggish kinetics. Hence, designing an efficient OER electrocatalyst, especially for alkaline water electrolysis that offers alternatives to the usage of precious group metals is a pressing priority. Herein, we report a novel nanocrystalline electrocatalyst consisting of two components, namely cobalt nickel phosphate and iron diselenide synthesised via a two-step electrodeposition at room temperature. The combination of the two components on the porous nickel foam substrate exhibits an overpotential of 272 mV at 100 mA/cm2 in 1 M KOH showing a low Tafel slope of a mere 38 mV/dec with appreciable retention even after 24 h of stability test at a relatively higher current density. The surface reconstruction that occurs when FeSe2 is electrodeposited on (Ni0.35Co0.65)3(PO4)2@NF and the synergy between the two components is the primary reason for the improved performance. Thus, this work highlights the ambient synthesis of a highly durable earth -abundant metal -based electrocatalyst which exceeds the performance of the standard Ru/C by a decent margin.
Keywords: Alkaline Water Electrolysis; Ambient synthesis; Electrodeposition; Non-PGM based Electrocatalyst; OER

Tensile nanostructured hierarchically porous non-precious transition metal-based electrocatalyst for durable anion exchange membrane-based water electrolysis - Singh, Kailash; Selvaraj, Kaliaperumal (Journal of Colloid and Interface Science, 2024)
Electrochemical water electrolysis is a promising method for sustainable hydrogen production while transiting towards hydrogen economy. Among many, the Anion Exchange Membrane (AEM) based water electrolyzer is an emerging yet potentially affordable technology on maturity for producing large-scale hydrogen accommodating the usage of Non-Platinum Group Metal (non-PGM) based inexpensive electrocatalysts. Herein, we demonstrate the excellent performance of a bifunctional Nickel Copper Phosphide-Nickel sulphide (NCP-NS) electrocatalyst with a unique tensile nanostructure obtained via a facile, controlled ambient galvanic displacement route. An AEM electrolyzer with a larger active area of 10 cm(2) stacked with the symmetric NCP-NS electrodes and a membrane demonstrates scalability with a requirement of a mere 1.66 V to reach a current density of 10 mA cm(-2). The nickel-copper phosphide boosts the kinetics of charge transfer between the electrode and electrolyte interface, while a unique combination of a few nickel sulphide phases present in the catalyst provides sufficiently appropriate active sites for the overall water electrolysis. For the first time, we report a room temperature performance of similar to 230 mA cm(-2) at 2 V for a non-PGM-based bifunctional electrocatalyst with exceptional durability for over 300 h of operation in an AEM water electrolyser with a retention rate of 95 %-97 % at a current density range of 80-800 mA cm(-2).
Keywords: AEM electrolyzer; Bifunctionality; Electrodeposition; Non-PGM based Electrocatalyst; stability